Development Prototype of IOT Based System to Monitor Agricultural Crops - Mohd Abbas, Mohamd Adli; Nazari, Ain (Evolution in Electrical and Electronic Engineering, 2025)
The agricultural sector in Malaysia is experiencing a significant decline in workforce participation, with the number of individuals decreasing from 554,247 in 2020 to 496,683 in 2021. Additionally, unpredictable climate changes have become a key factor manipulating environmental conditions, ultimately posing challenges to the agricultural sector. Therefore, this project is to develop an IoT-based prototype system designed to monitor and manage agricultural crops, focusing on maintaining optimal soil moisture levels and automating the watering process through a mobile application. The methodology involves the use of an ESP32 microcontroller integrated with soil moisture, temperature, humidity, and rain sensors. Data collected by these sensors is transmitted to the Blynk application, enabling users to remotely control water pumps and fertilizer mixers. The system automates irrigation and fertilization processes based on predefined conditions, optimizing water usage and improving operational efficiency. Experimental results demonstrate the system's effectiveness in maintaining ideal soil moisture levels between 50% and 70%, particularly for chili plants, ensuring proper delivery of water and nutrients while minimizing wastage. Thus, the innovation developed demonstrates how IoT technology can play a role in helping to address farmers' challenges. This leads to more efficient and sustainable practices to ensure better crop yields and the continuity of the agricultural sector in the future.